2010
DOI: 10.1128/mcb.01275-09
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ Activation Drives Increased Production of Autotaxin in Endothelial Cells and Lysophosphatidic Acid-Dependent Regression

Abstract: We previously reported that vascular endothelial growth factor (VEGF)-dependent activation of phospholipase C␥1 (PLC␥) regulated tube stability by competing with phosphoinositide 3-kinase (PI3K) for their common substrate. Here we describe an additional mechanism by which PLC␥ promoted regression of tubes and blood vessels. Namely, it increased the level of autotaxin (ATX), which is a secreted form of lysophospholipase D that produces lysophosphatidic acid (LPA). LPA promoted motility of endothelial cells, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…For instance, although the amount of VEGF produced by endothelial cells does not substantially contribute to the circulating level of VEGF (and is therefore considered to be small), it is nonetheless essential (38). Similarly, endogenously produced lysophosphatidic acid makes a vital contribution to instructing regression of endothelial cell tubes (39). These findings raise the possibility that angiomodulators that are produced by endothelial cells in response to lactate may make an important contribution to the angiogenic response despite the relative small quantity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although the amount of VEGF produced by endothelial cells does not substantially contribute to the circulating level of VEGF (and is therefore considered to be small), it is nonetheless essential (38). Similarly, endogenously produced lysophosphatidic acid makes a vital contribution to instructing regression of endothelial cell tubes (39). These findings raise the possibility that angiomodulators that are produced by endothelial cells in response to lactate may make an important contribution to the angiogenic response despite the relative small quantity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ATX regulates both prenatal lymphatic vessel formation in mice and zebrafi sh ( 79,80 ) and generates directional cues that direct primitive hematopoiesis and hemangioblast formation ( 81 ). Importantly, ATX can drive either vessel regression ( 82 ) or maturation ( 80 ) depending on the experimental context. It is likely that compartmentalization of ATX and its lipid substrates greatly infl uences biological function and activity because it generates high concentrations of lipid substrate in proximity to the membrane.…”
Section: Role In Physiology and Cancer Pathophysiologymentioning
confidence: 99%
“…We prepared HMREC tube lysates as described previously (10,12,21). Briefly, medium was removed, and the collagen gel sandwich was digested with two gel volumes of collagenase (type I from Clostridium histolyticum, Sigma-Aldrich) in Hanks' buffered salt solution supplemented with 100 M Na 3 VO 4 .…”
mentioning
confidence: 99%
“…Murine Retinal Explants-We prepared retinal explants as described previously (10,12,22). Immediately after euthanasia, the eyes were enucleated and kept in PBS.…”
mentioning
confidence: 99%
See 1 more Smart Citation